Remaking Culture on Wall Street A Behavioral Science Approach for Building Trust from the Bottom Up - Engler, Henry (Springer International Publishing, 2018)
Since 2008, financial firms have paid, in aggregate, in excess of $320 billion in fines related to misconduct. Nearly ten years later, while many large financial firms have increased their attention to bad behavior and cultural drivers, the degree of commitment and progress in these efforts has not been even across the industry. Serious or persistent misconduct continues in some firms. Many organizations have attempted to curb bad behavior through intrusive monitoring and enforcement actions which reflect a lack of trust in their employees. A different approach is needed, one that gets at the root causes of misconduct and attempts to rebuild culture from the bottom up, with the employee at the center. This is where tools from behavioral science can help senior risk officers, compliance and business heads better understand the mind-set of their employees and internal communities and create an environment where the link between ethical behavior and strong business results is promoted. If firms continue to fail in establishing stronger internal cultures, regulators may feel compelled to step in and dictate what they should do. This book emphasizes the need for a change in approach, looking at the increased incidence of misconduct and culture breakdown since the 2008 crisis, how regulators have responded, and includes a series of proposals to restore that trust and reform culture.